A three-generation family cluster with COVID-19 infection: should quarantine be prolonged?. (August 2020) - Yang, M.-C.; Hung, P.-P.; Wu, Y.-K.; Peng, M.-Y.; Chao, Y.-C.; Su, W.-L.
Abstract: Objectives: Families are a transmission route for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) because of the close contact. Monitoring of the viral load will be a valuable method to reduce the optimal number of quarantine days, especially in presymptomatic and symptomatic carriers of their households. The traditional three-generation families living together are seen frequently in East Asia, including in Taiwan. Study design: We report on a family cluster with six individuals infected with coronavirus disease in Taiwan. Methods: The current public policy in Taiwan is quarantine for at least 14 days, based on the incubation period, or until the patient has tested negative three days in a row using the SARS-CoV-2 reverse transcription polymerase chain reaction. Details on the onset date of clinical symptoms, throat swab conversion, and course of disease were collected from medical records retrospectively. Results: In the household of this three-generation Taiwanese family, the infection rate was 60%. The ratio of males to females was 4:2, and the age range was 11–85 years. The prevalence of asymptomatic disease was 33.3% (2/6). The longest throat swab conversion time was 37 days, and the estimated course of disease from symptoms to first conversion of throat swab was 59 days. Conclusions: Large families, including three-generation families in a single dwelling, should be monitored when the index case is found. Presymptomatic and symptomatic family members could be quarantined for an appropriate duration which, in our experience, is 2 months. Highlights: COVID-19 can be rapidly transmitted within a family. Presymptomatic and symptomatic family members should be quarantined. Two months is the recommended quarantine length based on the throat swab conversion.